Combinatorial application of tocotrienols and chemotherapeutic drugs enhances apoptosis and autophagy in colorectal cancer cells - Tham, Shiau Ying (2020)
Chemotherapy remains a cornerstone among the cancer treatment modalities but the therapeutic effectiveness of most conventional chemotherapeutic drugs is often limited by their dose-related toxicity. Tocotrienols, a class of vitamin E analogues, have been widely recognised as promising anti-cancer candidates due to their anti-proliferative, apoptotic, anti-invasive and anti-metastatic properties. Given that the multi-targeted actions of tocotrienols are suitable to be used as an adjunct treatment, a combinatory application with chemotherapeutic drugs in the cancer treatments may offer a synergism that provides augmented therapeutic effects and reduces high dose toxicities associated with chemotherapeutic drugs. Despite many combination studies with tocotrienols were conducted previously, the combined treatments of δ-tocotrienol (δT3) and conventional chemotherapeutic drugs, namely 5-fluorouracil (5FU) and doxorubicin (Dox) have not been reported in colorectal cancer cells. Hence, the current study aimed to study the therapeutic effects of δT3 + 5FU and δT3 + Dox combined treatments as an enhanced cancer therapeutic approach on Caco-2 and SW48 colorectal cells.